Optical Properties of Dye-Filled Polymer Films Deposited in Vacuum - Grytsenko, K.; Navozenko, O.; Kolomzarov, Yu.; Kryuchin, A.; Tolmachev, O.; Slominsky, Yu.; Kurdukov, V.; Ksianzou, V.; Schrader, S. (Реєстрація, зберігання і обробка даних, 2012)
The results of investigating properties of polytetrafluoroethylene (PTFE) and polyparaphenylene sulphide (PPS) films filled with dye molecules by co-deposition in vacuum are given. Thin polymer films filled with different polymethine dyes with various dye concentration are investigated. Film properties at room temperature and during heating were studied using optical absorption spectroscopy. It is shown that the polymer matrix prevented dye molecules aggregation, particularly the PTFE matrix prevented aggregation more strongly than the PPS matrix. During heating the PTFE matrix keeps the dye molecules in non-aggregated state up to dye decomposition temperature. Представлено результати дослідження властивостей плівок політетрафторетилену (ПТФЕ) та поліпарафенілен сульфіду (ППС), які були наповнені молекулами барвників за допомогою співосадження у вакуумі. Досліджено тонкі полімерні плівки, що наповнені різними поліметиновими барвниками з різними концентраціями. Властивості плівок при кімнатній температурі і під час нагрівання було вивчено з використанням оптичної абсорбційної спектроскопії. Показано, що полімерна матриця запобігає агрегації молекул барвника, зокрема ПТФЕ-матриця запобігає агрегації сильніше ніж ППС-матриця. Протягом нагрівання ПТФЕ-матриця утримує молекули барвника в не агрегованому стані до температури розкладання барвника. Представлены результаты исследования свойств пленок политетрафторэтилена (ПТФЕ) и полипарафенилен сульфида (ППС), которые были наполнены молекулами красителя с помощью соосаждения в вакууме. Исследованы тонкие полимерные пленки, наполненные разными полиметиновыми красителями с различными концентрациями. Свойства пленок при комнатной температуре и при нагревании были изучены с использованием оптической абсорбционной спектроскопии. Показано, что полимерная матрица предотвращала агрегацию молекул красителя, в частности ПТФЕ-матрица предотвращала агрегацию молекул более сильно, чем ППС-матрица. Во время нагревания ПТФЕ-матрица удерживала молекулы красителя в не агрегированном состоянии до температуры разложения красителя.